Pengaruh Penggunaan Pasir Putih Sebagai Bahan Campuran Beton Mutu Tinggi - Meisye Mitha Siranga; Suryanti Rapang Tonapa; Frans Phengkarsa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The use of concrete in Indonesia cannot be separated from skyscrapers, bridges with long spans, and underground buildings which generally have a larger load, so the use of high-strength concrete is necessary. This study aims to determine the value of compressive strength, split tensile strength, flexural strength, modulus of elasticity of concrete and determine the workability of fresh concrete with the addition of 0.8% superplaticizer. The test objects used in the form of cylinders with a diameter of 15 cm and a height of 30 cm as many as 15 pieces, and 3 pieces of blocks measuring 15 cm × 15 cm × 60 cm. From the results of the study, the compressive strength value was 43,007 MPa. The split tensile strength test is 3.584 MPa. The flexural strength test is 4,340 MPa. The elastic modulus test is 28447.956 MPa. From the slump test on fresh concrete with the addition of a superplaticizer, it is obtained by 10 cm.